Metaphorical expressions used in Swedish news media narratives to portray the shortage of nurses and their working conditions. (26th October 2015) - Blomberg, Helena; Stier, Jonas
Abstract: Aim: The aim of the study is to uncover and reveal how nurses as a profession and their working conditions are dramatized and portrayed in Swedish media narratives about the shortage of nurses. Background: The media is an arena where stakeholders can air their views of the healthcare sector in general and the situation for nurses in particular. The focus in this study is the debate in Sweden on the shortage of nurses. Design: Qualitative discursive study. Method: A discourse analysis of media narratives about nurses and their working conditions published in several Swedish newspapers from 2009–2014. 1779 articles were included in the study. A selection (113 articles) of these articles was further analysed using a qualitative discursive psychological approach. Findings: Nurses are portrayed as being good, concerned about and critical of healthcare managers and politicians for not taking action. The accused actors justify their actions by partially accepting or displacing responsibility. The shortage of nurses is framed as a social problem – a threat to patients' safety. Seven different types of metaphorical expression frame the problem as inevitable, beyond control, abstract, an individual and collegial problem and nurses as replaceable. In addition, nurses and patients are dehumanized and no‐one is held responsible. Conclusions: This study analyses the role of the media in emphasizing the seriousness or obscurity of the problem and possible solutions to it. Alternative narratives are needed to re‐frame the nursing shortage and to find sustainable solutions.